Sarcopenia as a Prognostic Factor and Multimodal Interventions in Breast Cancer - Du L; Liu X; Zhu Q; Zhu K; Li P (International Journal of General Medicine)
Ludi Du, Xiang Liu, Qiaoli Zhu, Kuangye Zhu, Ping Li Department of Thyroid and Breast Surgery, Quzhou People’s Hospital, Quzhou, 324000, People’s Republic of ChinaCorrespondence: Ping Li, Department of Thyroid and Breast Surgery, Quzhou People’s Hospital, Quzhou City, Zhejiang Province, 324000, People’s Republic of China, Email li_ping33@163.comObjective: This study aims to demonstrate the impact of sarcopenia on the prognosis of early breast cancer and its role in early multimodal intervention.Methods: The clinical data of patients (n=285) subjected to chemotherapy for early-stage breast cancer diagnosed pathologically between January 1, 2016, and December 31, 2020, in our hospital were retrospectively analyzed. Accordingly, the recruited subjects were divided into sarcopenia (n=85) and non-sarcopenia (n=200) groups according to CT diagnosis correlating with single-factor and multifactorial logistic regression analyses. Further, the breast cancer patients combined with sarcopenia were randomly divided into multimodal, nutritional, exercise, and control intervention groups. Multimodal interventions combined supervised exercise programs and tailored nutritional support. The preliminary data and post-operative efficacy, as well as post-operative survival of patients of the four groups, were compared.Results: Sarcopenia significantly reduced overall survival (OS) rates at 1 year (82.94% vs 85.78%), 3 years (81.76% vs 83.91%), and 5 years (80.59% vs 81.17%) compared to non-sarcopenia patients (P< 0.001). Patients in the multimodal intervention group showed better outcomes, including improved ALB levels, reduced complication rates (4.5% vs 18.18% vs 18.18% vs.52.63%), and fewer chemotherapy side effects. The multifactorial stepwise logistic regression analysis indicated that advanced age (OR: 1.512, 95% CI: 1.178– 1.962, P < 0.001) and multimodal intervention pathways (OR: 5.333, 95% CI: 2.651– 10.473, P < 0.001) were significant risk factors affecting patients’prognosis.Conclusion: Sarcopenia might be an independent risk factor leading to the increase of post-operative complications and the shortening of long-term survival of patients. Moreover, the multimodal intervention of nutrition combined with exercise could effectively improve the quality of the prognosis of patients with important clinical significance.Keywords: sarcopenia, early breast cancer, prognosis, influencing factors, multimodal interventions